1966
DOI: 10.1113/jphysiol.1966.sp008111
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatation in the submaxillary gland of the rabbit

Abstract: SUMMARY1. In the rabbit, in contrast to the cat and dog, the vasodilatation and the secretion in the submaxillary gland which accompany parasympathetic nerve stimulation are correspondingly sensitive to atropine block.2. It is concluded that true vasodilator nerve fibres to the submaxillary gland exist in the chorda tympani nerve of the rabbit.3. The vasodilatation which follows sympathetic vasoconstriction in the submaxillary gland of the rabbit is small and variable. The possibility that this after-dilatatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1968
1968
1987
1987

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…Stimulation of chorda tympani nerve leads to vasodilatation in these glands in the dog, cat and rabbit (Morley, Schachter & Smaje, 1963;Bhoola, Morley & others, 1965;Schachter, 1966). The cause of this vasodilatation is in dispute.…”
Section: Discussionmentioning
confidence: 93%
“…Stimulation of chorda tympani nerve leads to vasodilatation in these glands in the dog, cat and rabbit (Morley, Schachter & Smaje, 1963;Bhoola, Morley & others, 1965;Schachter, 1966). The cause of this vasodilatation is in dispute.…”
Section: Discussionmentioning
confidence: 93%
“…There is a possibility that each of these three kinds of neural information conveyed via the three types of preganglionic fibres control the physiological functions of the submandibular gland differentially because of the following notions. Although functional characteristics of a synaptic connexion between pre-and post-ganglionic fibres have not been studied yet in submandibular ganglions of rabbits, intracellular recordings from submandibular ganglions of rats revealed that about 75 % of the post-ganglionic fibres were connected with a single preganglionic fibre (Suzuki & Sakada, 1972;Lichtman, 1977), and the parasympathetic neural information is conducted to the three main effectors in submandibular glands such as the myoepithelial cells, blood vessels and secretary cells through submandibular ganglions in rabbits, cats and dogs (Morley, Schachter & Smaje, 1966;Emmelin et al 1968Emmelin et al , 1969Freitag & Engel, 1970;Garrett, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion extended Barcroft's (1914) view that functional vasodilatation was caused by the secretorv metabolic activity of the gland cells, by implicating kallikrein as the hitherto unidentified metabolic mediator of vasodilatation. The view that kallikrein released into the interstitial fluid during secretion was the physiological mediator of functional vasodilatation not only in the salivary glands, but also in sweat, pancreatic and other glands, has since been maintained by some workers (Hilton & Lewis, 1955 a, b;1956;Fox & Hilton, 1958;Hilton & Jones, 1963) and opposed by others (Bhoola, Morley & Schachter, 1962;Bhoola, Morley, Schachter & Smaje, 1965;Morley, Schachter & Smaje, 1966;Webster, 1966;Skinner & Webster, 1968;Schachter & Beilenson, 1967).…”
Section: Introductionmentioning
confidence: 99%